Assessment of Science, Technology, Engineering and Mathematics Strand of the K-12 Program among Selected Public Schools in Zone 2 Division of Zambales - Honrado, Lyra Castillo; Calimlim, Adelia D. (Future Science / FSH-PH Publications, 2021)
The study determined the impact of the STEM Strand implementation of senior high schools in the Division of Zambales. The study was limited to fifty secondary public-school teachers in Zone II.The study revealed that majority teacher-respondents, are generally young with only a minimum number of trainings attended. STEM trends, there were more males than females and a larger are married. There were no significant differences in the success of the STEM schools in Palauig, Botolan and Iba in the following domains:college preparation;integrated and innovative technology use; STEM-rich informal experiences; connections with industry and the world of work; well-prepared STEM teachers and professionalized teaching staff and positive school community and culture of high expectations for all. Based on the summary of findings and the conclusions arrived at, the researcher has offered the following recommendations that professional learning in the form of learning action cells and lesson study should be provided to relatively novice STEM teachers in order to expose them to effective instructional strategies and impact their actual classroom practices as opposed to cascading in-service trainings. Greater involvement of these partners through planning, implementation, and review should be targeted instead of only involving them for immersion activities. A more intensive evaluation of the STEM implementation following the Context-Input-Process-Product approach should be conducted to strengthen and confirm the findings of the study. A more study that would monitor the whole system as opposed to the present investigation’s focus on teacher perception would lend greater credence to the results.